Pension and Health Services Utilization: Evidence from Social Pension Expansion in China - Shanquan Chen; Xi Chen; Stephen Law; Henry Lucas; Shenlan Tang; Qian Long; Lei Xue; Zheng Wang (Global Labor Organization (GLO), 2020)
The proportion of people aged 60 years or over is growing faster than other age groups. The well-being older adults depend heavily on their state of health. This study evaluates the effects of pensions on older adults' health service utilization, and estimates the size of pension required to influence such utilization. Using a nationally representative survey, the China Health and Retirement Longitudinal Study (CHARLS), we adopted a fuzzy regression discontinuity design and undertook segmented regression analysis. Pension demonstrated heterogeneous effects on health service utilization by income. We show that pension encouraged low-income individuals to use both outpatient (OR = 1.219, 95% 1.018-1.460) and inpatient services (OR = 1.269, 95% 1.020-1.579). In the meantime, it promoted self-treatment, specifically over-the-counter (OR = 1.208, 95% 1.037-1.407; OR = 1.206, 95% 1.024-1.419; respectively) and traditional Chinese medicines (OR = 1.452, 95% 1.094-1.932; OR = 1.456, 95% 1.079-1.955; respectively) among all income groups. However, receiving a pension had no effect on the frequency of outpatient or inpatient service use. Breakpoints for pension to promote health service utilization were mainly located in the range 55-95 CNY (7.1-12.3 EUR or 8.0-13.8 USD). Our study enriches the literature on pension and healthcare-seeking behaviour, and can be helpful in policy design and model formulation.
Keywords: I11; I18; J14; H55; 330; pension; health services utilization; regression discontinuity design; segmented regression